Assessment of Functional Outcome of Distal Radius Fracture Treated with Kirschner’s Wire - Kandel, Sandip; Shrestha, Dinesh Kumar; Karki, Prateek; Shrestha, Sabin; Yogi, Sushil (Journal of Nepalgunj Medical College, 2023)
Introduction: Distal radial fractures are most common fracture which accounts 8-15 % of all bony injuries. There is a wide variety of treatment options and selection mainly depends on age, occupation, type of fracture. Fracture realignment is most important element for good functional outcome. Closed reduction and percutaneous k-wire fixation is most convenient method as it is cost effective. Aims: To evaluate the functional outcome of distal radial fractures treated with closed reduction and percutaneous pinning. Methods:This prospective observational study was conducted in Nepalgunj medical college Teaching hospital, Kohalpur from September 2021 to August 2022. Patient aged above 18 and below 70 years who had isolated distal radius fracture with k wire fixation. Functional results were assessed at a follow up of 6 months, by modified Gartland and Werley scoring system. Results: In this study out of 45 cases there were male preponderance 29 (65%). The mean age of our patient was 36.8 (SD±12.80) years. K-wires were removed between four to six weeks of operation depending upon the union and followed for six months. On final follow up variables assessed according to Modified Gartland and Werley scoring system which shows, 25 patients had excellent (51.11%) and 13 good (33.33%) functional outcome. Overall, 84.44% of the patients achieved an excellent to good functional outcome. Still residual pain and dorsal angulation were complications post-operatively and was in acceptable limits in majority of cases. Conclusion: Closed reduction and percutaneous pinning for distal radius fractures have shown to achieve good functional outcome. Most of the complications after the procedure were within the acceptable limits. Further studies are required to assess its efficacy in various other fracture types.